Antecedents and consequences of islamic bank performance based on the maqashid sharia index - Kautsar Riza Salman (The Indonesian Accounting Review, 2023)
This study aims to obtain empirical evidence regarding the antecedents and consequences of performance based on the maqashid sharia index in Islamic banks in Indonesia. The maqashid sharia index in the literature and previous empirical research is limited to its use in the aspect of performance measurement only. This study seeks new insights into the antecedents and consequences of Islamic bank performance based on the Islamic maqashid index. The antecedent studied is the characteristics of the sharia supervisory board, while the consequences studied are Islamic social reporting. This study examines the effect of the sharia supervisory board on the maqashid sharia index in Islamic banks in Indonesia. In addition, this study also examines the effect of the maqashid sharia index on Islamic social reporting. The research sample is 11 Islamic banks in Indonesia within four years (2015-2018). This study found that the characteristics of the sharia supervisory board had a significant effect on the maqashid sharia index. The better the characteristics of the sharia supervisory board the higher the maqashid sharia index is. In addition, the maqashid sharia index has a significant effect on Islamic social reporting, meaning that the higher the maqashid sharia index, the better Islamic social reporting. The first implication is that it requires Islamic banks to pay attention to fair returns, avoid prohibited products and services, and eliminate harmful elements that result in injustice. The second implication is that it requires Islamic banks to seek to increase their profitability, redistribution of profits and welfare, and investment in the real sector.